Clinical Implications of Adipocytokines and Newly Emerging Metabolic Factors with Relation to Insulin Resistance and Cardiovascular Health - Choi, Sung Hee; Hong, Eun Shil; Lim, Soo (Frontiers in Endocrinology, 2013)
Adipose tissue is known to secrete hormones actively and produces many biologically active proteins called adipocytokines. Typically, obesity is followed by low-grade inflammation, which is characterized by increased circulating levels of pro-inflammatory cytokines. Macrophages play a role in the inflammatory process by secreting many cytokines such as tumour necrosis factor-alpha, interleukin-6, resistin and retinol binding protein-4. These cytokines and chemokines participate in low grade pro-inflammatory processes leading to insulin resistance, metabolic impairment and cardiovascular diseases. More metabolic regulators, such as fibroblast growth factor (FGF)21, FGF19, FGF1, vaspin and visfatin have now been discovered but their exact roles in human diseases are still unclear. This review focuses on recent research regarding the role of adipokines and new metabolic factors in metabolic derangement or cardiovascular disease.